Local governance and community capacities : search for new frontiers - Rahman, Hossain Zillur, 1951-; Islam, S. Aminul (Dhaka, Bangladesh : University Press, 2002)
With reference to Bangladesh.
Includes bibliographical references and index.
Keywords: Municipal government -- Bangladesh; Public administration -- Bangladesh